Impact of antithrombotic therapy in the prognosis of atrial fibrillation patients with advanced chronic kidney disease. (25th November 2020) - Andreu Cayuelas, J.M; Raposeiras-Roubin, S; Fortuny Frau, E; Garcia Del Egido, A; Seller-Moya, J; Ortiz Cortes, C; Camacho Freire, S.J; Alonso Fernandez, P; Jorge-Perez, P; Lopez-Pais, J; Bravo-Marques, R; Palacios-Rubio, J; et al.
Abstract: Introduction: Chronic kidney disease (CKD) is associated with an elevated thromboembolic and bleeding risk in atrial fibrillation (AF) patients, so the decision of antithrombotic therapy is a challenge. Purpose: To analyze mortality, embolic and bleeding events in patients with advanced CKD and AF. Methods: Multicentric retrospective registry on patients with AF and advanced CKD (CKD-EPI <30 mL/min/1.73 m 2 ). For death, multivariable Cox regression analysis was developed. For embolic and bleeding events, competing-risks regression based on Fine and Gray's proportional subhazards model was performed, being death the competing event Results: We analysed 405 patients with advanced CKD and newly diagnosed AF. 57 patients were not treated with antithrombotic therapy (14.1%), 80 only with antiplatelet/s (19.8%), 211 only with anticoagulation (52.1%), and 57 with anticoagulant plus antiplatelet/s (14.1%). During a follow-up of 4.6±2.5 years, 205 died (50.6%), 34 had embolic events (8.4%) and 85 had bleeding outcomes (21.0%). Bleeding event rate was significantly lower in patients without antithrombotic therapy (Figure). After multivariate analysis, anticoagulant treatment was associated with higher bleeding rates, without differences in mortality or embolic events (Table). Conclusion: Anticoagulation therapy was associated with a significant increase in bleeding events in patients with advanced CKD and newly diagnosed AF. None of the antithrombotic therapy regimens resulted in lower embolic events rate neither benefit in mortality. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): This study was supported by an unconditional grant from BMS-Pfizer